Modulation of gut microbiota and serum metabolome by Apostichopus japonicus derived oligopeptide in high-fructose diet-induced hyperuricemia in mice - Jun Zhou; Ziyan Wang; Zhixuan Zhang; Jiaojiao Han; Ying Feng; Jing Zhang; Zhen Zhang; Ye Li; Tinghong Ming; Chenyang Lu; Rixin Wang; Xiurong Su (Food Science and Human Wellness)
Fructose consumption has risen dramatically in recent decades due to the use of sucrose and high fructose corn syrup in beverages and processed foods, contributing to rising rates of hyperuricemia. The purpose of this experiment was to explore the anti-hyperuricemia effects of an active oligopeptide (GPSGRP) derived from sea cucumber in fructose induced hyperuricemia mouse model, and to clarify the underlying mechanism in sight of gut microbiota and serum metabolites. Peptide GPSGRP treatment rebalanced uric acid metabolism and alleviated inflammatory response in mice. In addition, treatment with GPSGRP decreased the abundance of Bacteroides and Proteobacteria at the phylum level, Muribaculum, Prevotella and Bacteroides at the genus level, and inhibited the related pathways of purine metabolism and glycolysis/gluconeogenesis metabolism. Moreover, serum metabolites, including linoleic acid, indole and its derivatives, arachidonic acid and uridine, as well as related metabolic pathways, such as tricarboxylic acid cycle, ketone production and sugar production, were altered in response to GPSGRP treatment. This study provides a valuable reference for the application and development of marine biological peptides in uric acid management.